Practical concepts for the use of probabilistic methods in the structural analysis and reassessment of existing bridges - presentation of latest research and implementation - Thomas Braml; Christian Kainz (Acta Polytechnica CTU Proceedings, 2022)
In structural engineering and bridge construction, probabilistic calculations are only performed in a few exceptional cases. The ability to directly use information from the existing structure is an important advantage of probabilistic methods. Geometric data or the position and quantity of the installed reinforcing steel and tendons can be measured. Results from monitoring of the traffic can be used to generate structure-specific load models. Many clients are still very sceptical about the results of probabilistic calculations, even though there are several examples of successful application. The use of probabilistic verification formats is explicitly permitted by the German guideline for the assessment of existing bridges (German: Nachrechnungsrichtlinie). Since a high degree of special knowledge is required for the application of probabilistic calculations, it is difficult to establish the potential of this verification method in practice. It is necessary to enable the practical engineer to utilize the advantages of probabilistic calculations and to include the actual structural conditions into the calculation model, but without the need for all the special knowledge. Structure-specific partial safety factors include measured data and can be used for the well-known and in the codes established semi-probabilistic design concept. The authors present examples for the successful application of probabilistic methods and of data measurement during the reassessment of two existing bridges in Germany. The capabilities of full-probabilistic calculations for the reassessment of existing structures are described and concepts for the calculation of structure-specific partial safety factors are shown.